Multicenter Study of Pyruvate Kinase Deficiency in Argentina - Pepe, C.; Eberle, S. Eandi; Donato, H.; Basack, N.; Baña, M.F. Tisi; Cedola, M.A.; García, E.; Rapetti, M.C.; Rubulotta, E.; Milanesio, B.; Bisio, A. Maquijo; Cichierichetti, M.A.; et al. (Journal of Hematology Research, 2022)
The red blood cell (RBC) pyruvate kinase deficiency (PKD) is the most common recessive congenital defect of glycolytic enzymes associated with non-spherocytic hemolytic anemia. It is a rare hereditary disorder caused by >300 variants in the PKLR gene. This is a retrospective study of 19 patients from different centers from Argentina with confirmed molecular diagnosis of PKD. Clinical follow-up was carried out from birth in most cases. Five consanguineous patients from “gypsy” community, were homozygous for the “PK-Gypsy deletion” (PK-Gd). During the neonatal period they developed anemia with icterus. Transfusion exchange was required in 60%, light therapy in 80%, and RBC transfusion in 80%. During the follow-up iron overload was detected in the 100%, cholecystectomy was indicated in 40%, and splenectomy in 60%. Thirteen cases had 2 missense variants (MS), being the Mediterranean variant (p.Arg486Trp) the more frequent detected (26%).Only 1 patient had a missense-splicing mutation combination. During the neonatal period, 86% had anemia and icterus. Light therapy was required in 78%, transfusion exchange in 21% and RBC transfusion in 64%. During the follow-up iron overload was detected in 57% and splenectomy was indicated in 43%. Transfusions (pre-splenectomy and post-splenectomy) were more required in PK-Gd cases as compared with patients with point mutations (100%/60% vs 71%/29% respectively). Our data indicates a high clinical-therapeutic-molecular heterogeneity in PKD patients with the PK-Gd group presenting the most severe cases.